2021
DOI: 10.1038/s41398-020-01190-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of poor psychiatric status and sleep quality among frontline healthcare workers during and after the COVID-19 outbreak: a longitudinal study

Abstract: Poor psychiatric status and sleep quality were common among frontline healthcare workers (FHWs) during the outbreak of the 2019 novel coronavirus disease (COVID-19), but the change in these mental health outcomes overtime remained unknown. This study compared the psychiatric status and sleep quality of FHWs during and after the COVID-19 outbreak in China. FHWs who volunteered to work in Hubei province (the COVID-19 epicenter) were assessed at baseline during the COVID-19 outbreak and re-assessed when they retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
3
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 44 publications
9
40
3
9
Order By: Relevance
“…Another online survey showed that the prevalence of DEP, ANX, insomnia, and distress symptoms were 50.7, 44.7, 36.1, and 73.4%, respectively, among frontline healthcare workers in China (21). Based on this study, health authorities, academic institutions and societies in China rapidly developed various measures and responses including, education materials and programs, 24 h hotline services, on-site crisis psychological interventions, and relevant research (12). Consequently, the prevalence of psychiatric problems among frontline healthcare workers gradually declined in subsequent studies (22).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Another online survey showed that the prevalence of DEP, ANX, insomnia, and distress symptoms were 50.7, 44.7, 36.1, and 73.4%, respectively, among frontline healthcare workers in China (21). Based on this study, health authorities, academic institutions and societies in China rapidly developed various measures and responses including, education materials and programs, 24 h hotline services, on-site crisis psychological interventions, and relevant research (12). Consequently, the prevalence of psychiatric problems among frontline healthcare workers gradually declined in subsequent studies (22).…”
Section: Discussionmentioning
confidence: 83%
“…They found that medical health workers had psychosocial problems and risk factors for developing them. A report conducted in Wuhan found that poor mental status and sleep quality were common among frontline healthcare workers during the COVID-19 outbreak (12). However, there are some limitations in the sample size and sampling representativeness of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al observed a reduction in acute symptoms of stress recorded online by nurses in a large Chinese hospital in January and February 2020, corresponding to the attack and stationary phases of the pandemic [24]. Other researchers focused on sleep quality [25] and the effectiveness of cognitive behavioral therapy to prevent symptoms of stress [26]; on resilience [27,28]; on the relationship between leadership style and psychological safety and distress [29], and on the gradual adaptation of personnel to new safety procedures, with a reduction in anxiety and stress levels [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…There are currently limited published longitudinal studies amongst frontline HCWs to quantify the ongoing psychological impact of COVID-19 even as the pandemic situation waxes and wanes. Two large prospective longitudinal studies amongst Chinese frontline HCWs showed slightly different outcomes: one study [ 9 ] found significantly worse psychiatric status (somatization, obsessive-compulsiveness, interpersonal sensitivity, depression, anxiety, hostility, phobic anxiety, paranoid ideation, psychoticism) and sleep quality a month later; and the other [ 5 ] found significantly higher risks for depression, anxiety and PTSD symptoms during the outbreak period compared to the stable period of the pandemic a month later. On a smaller scale, a study in Belgium [ 10 ] amongst Intensive Care Unit (ICU) nurses in April 2020 showed that they had improved depression, anxiety and somatization over a two-month period.…”
Section: Introductionmentioning
confidence: 99%